أوجه عناية العلماء بعلم فضائل القرآن الكريم: Knowledge of the virtues of the Noble Qur’an and aspects of care for it - Ali Khousrof, Marwah Mohsen; Abdo Khaled, Nashwan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص تناولت هذه الدراسة علم فضائل القرآن الكريم وأوجه العناية به عن طريق التعريف بهذا العلم، وأهميته، وبداية نشأته وتأليف العلماء فيه، ومميزات التأليف في علم فضائل القرآن، ثم ذكرت أنواع فضائل القرآن وقد تم تقسيمها إلى ثمانية أقسام، وقد تعرضت الدراسة لبعض المسائل المتعلقة بعلم فضائل القرآن؛ كحكم المفاضلة بين سورة القرآن الكريم، وكيفية الاستفادة من الفضائل، والأخذ بالفضائل المروية في فضائل القرآن الكريم، وحكم العمل بالحديث الضعيف الوارد فيها، وأن العلماء لم يلتزموا في تناول فضائل القرآن الكريم طريقة محددة، ولم يسيروا في التصنيف سيرة واحدة، فقد تعددت طرقهم في عرضه. Abstract This study dealt with the science of the virtues of the Noble Qur’an and the aspects of care for it by defining this science, its importance, the beginning of its inception and the authorship of scholars in it, and the advantages of authorship in the science of the virtues of the Qur’an. related to the science of the virtues of the Qur’an; Such as the ruling on the comparison between Surah the Noble Qur’an and how to benefit from the virtues, adopting the virtues narrated in the virtues of the Noble Qur’an, and the ruling on working with the weak hadith contained in it, And that the scholars did not adhere to a specific method in dealing with the virtues of the Noble Qur’an, and did not follow the classification in one biography.